﻿How AI Helps the Best and Hurts the Rest - Otis, Nicholas; Clarke, Rowan; Delecourt, Solène; Holtz, David; Koning, Rembrand (MIT Sloan Management Review, 2026)
Can generative AI serve as an on-demand business adviser? A field experiment with hundreds of small business owners in Kenya found that AI access boosted revenues and profits by 15% for high performers — but caused a nearly 10% decline for those who had already been struggling. The culprit: Weaker performers followed generic or misleading AI advice because they lacked the judgment to filter it out. Leaders deploying AI at scale must design their rollouts carefully to avoid widening performance gaps.